Effect of a zinc amino acid complex on egg production, egg shell quality and external appearance in two laying hen genotypes housed in two different production systems - Boyner, Malin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2015)
With an extended production cycle up to 100 weeks of age, the yearly number of layer chickens hatched and reared can be reduced, and in turn so can the euthanasia of day-old male chickens. Lately, the interest for keeping laying hens for a prolonged production cycle has increased in Sweden as well as in other European countries. However, concerns exist regarding how prolonged laying cycles affect egg quality, animal welfare as well as producer economy. In this trial, the two commercial hybrids LSL Classic and Bovans Robust were housed in furnished cages and a single tier floor production system. In addition to the effects of age, an organic mineral complex with a hypothesized positive effect on egg quality, integument and skeletal condition was evaluated. The study was conducted during 20-61 weeks of age. There were no consistent effects of the mineral amino acid complex supplementation on either egg quality, plumage condition or keel bone deformities at a hen age of 55 weeks. However, there were a lot of differences between hybrids regarding egg composition and layer performance in the two production systems. As expected and concluded in earlier research; egg shell quality, plumage condition and keel bone deformities were negatively affected by increased hen age.